A multifaceted approach to legal pluralism and ethno-cultural diversity. Issue 1 (2nd January 2016) - Macioce, Fabio
Abstract : In this paper, I argue that, in order to balance internal cohesion and ethno-cultural diversity in pluralistic communities, a multifaceted approach would be useful. Such an approach puts side by side the recognition of some group rights, a form of joint governance with group authorities, and a judicial mechanism that allows culturally sensitive interpretations of constitutional principles. I suggest that, even though in some social arenas (family, child education, food traditions, and immigration), it would be possible to enforce some kind of form of joint governance; in some situations, it would be useful to have a more nuanced system of legal interpretation, especially when the former solution is somehow impossible. That system, I argue, can be similar to the margin of appreciation doctrine, which the European Court of Human Rights has adopted in order to balance rights' enforcement and national traditions.